Kyrgyz Republic : Request for Purchase Under the Rapid Financing Instrument and Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; Informational Annex; and Debt Sustainability Analysis. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Kyrgyz Republic's Request for Purchase Under the Rapid Financing Instrument and Disbursement Under the Rapid Credit Facility. The COVID-19 pandemic has been hitting the Kyrgyz economy very hard and created an urgent balance of payments need. All sectors are being impacted with extreme severity as measures are being taken to stop the spread of the virus. Given the unprecedented high level of uncertainty, IMF emergency support under the Rapid Financing Instrument and the Rapid Credit Facility helps provide a backstop and increase buffers and shore up confidence. It also helps to preserve fiscal space for essential COVID- 19-related health expenditure and catalyze donor support. Banks' capital and liquidity buffers need to be used to absorb credit losses and the liquidity squeeze. Once these buffers are exhausted, the central bank needs to show flexibility on the timing of bringing capital and liquidity above the minimum required, considering the length of the crisis. Expeditious donor support is needed to close the remaining balance of payments gap and ease the adjustment burden.